Decolonial process tracing: Indigenous rights and pipeline resistance movements. Issue 1 (March 2023) - Awasis, Sakihitowin
This article explores how decolonial methodologies and Anishinaabe gkendaasowin (ways of knowing) can augment detailed narrative process tracing methodologies used to examine social and political processes. While detailed narrative is most frequently used as a tool of causal inference, focusing on the unfolding of a singular time, I see potential for it to be enriched by Indigenous legal traditions that emphasize epistemic diversity and multiple temporalities. Analyzing how Indigenous rights are leveraged in decision-making processes for the Line 9 and Line 3 pipelines, I show how a decolonial approach to process tracing (DPT) that centers Anishinaabe gkendaasowin can change both the actors and power relations involved. Recognizing that energy decision-making processes take place alongside, outside, and within colonial state institutions, and are embedded in the land as constellations of reciprocal kinship responsibilities, DPT opens space to examine two kinds of Indigenous rights: those acquired through struggle with state institutions, and those inherent to Indigenous communities' attachment to place. DPT addresses the shortcomings of a focus on linearity by privileging inherent rights that are often excluded from detailed narrative process tracing. To take inherent rights seriously, one must also take more-than-linearity and more-than-humans seriously—and DPT is uniquely positioned to do this. The key features I propose for decolonial process tracing are grounded constellations, multiversality, and multitemporalities. Decolonizing methodologies and Anishinaabeg studies provide direction for more expansive, decolonial process tracing techniques which can in turn help understand the relationship between temporalities, law, and energy governance.